Anticancer Activity of Spirulina Cultivated in Walne and Organic Media - Putriana Sari Sirait; Iriani Setyaningsih; Kustiariyah Tarman (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Spirulina is Cyanobacteria containing active components which is potentially showing anticancer activity. The purposes of this study were to determine anticancer activity and selectivity of crude extractsof Spirulina cultured using Walne and organic media, and to detect the apoptosis. The stages of this study included cultivation and harvesting of Spirulina, active components extraction, anticancer test and apoptosisdetection. Anticancer activity was determined using MTT assay. The crude extracts of Spirulina from Walne and organic cultures contained active components of alkaloids, flavonoids, steroids, and saponins. Theseextracts were not toxic to normal breast cells (MCF-12a), but showed cytotoxic activity in breast cancer cells (MCF-7). The crude extract of Spirulina from Walne culture had IC50 value of 36.23 ppm and selectivity index 30.07, while the IC50 of organic culture was 117.78 ppm and selectivity index 7.17. Detection of apoptosis with Hoechst dye 33342 showed the apoptotic activity of Spirulina crude extract against MCF-7 cells.